The political economy of governance in a 'global value chain world'. Issue 2 (4th March 2017) - Mayer, Frederick W.; Phillips, Nicola; Posthuma, Anne C.
ABSTRACT: The global political economy has come to be shaped by a historically novel form of industrial organisation, the global value chain (GVC). Yet, although there has been much attention both to GVCs and to global governance, there has been a great deal less that connects the two. This symposium aims to take a step towards redressing this situation in order to move towards a better understanding of the political economy of governance in a 'GVC world'. This introductory essay outlines the aims of the Symposium as being (a) to advance a more encompassing vision of politics and agency in a GVC world, (b) to understand the implications of a GVC world for global economic governance and (c) to move beyond empirical description and conceptual characterisation of forms of governance towards more explicit normative considerations of their implications for more equitable and sustainable outcomes.